Fault isolation in a case study of failure analysis on Metal–Insulator–Metal capacitor structures. Issue 9 (August 2015) - Giuffrida, V.; Barbarino, P.; Muni, G.; Calvagno, G.; Latteo, G.; Mello, D.
Abstract: Metal–Insulator–Metal (MIM) capacitors are extensively used in many microelectronic products such as BICMOS for automotive radar applications, but failure analysis process is very laborious due to peculiar structure. In this paper a possible fault isolation process flow was shown in a failure analysis case study. In particular due to the fact that it is a customer return device, many checks were done in fault isolation steps before physical analyses. Finally a FIB cross section was performed on OBIRCH hot spot and the results confirmed the validity of the fault isolation process. Highlights: We illustrate a possible fault isolation process flow in a failure analysis case study on MIM capacitors structures. The difference among delayering methods previously described is shown. The difficulties related to the localization of the defect in the large area of capacitors are reported.